Review on comparative study of dry and wet torrefaction. (December 2015) - Acharya, Bimal; Dutta, Animesh; Minaret, Jamie
Abstract: Torrefaction is a mild pyrolysis process used to improve the fuel quality of biomass so that it becomes a more appropriate solid fuel for coal fired power plants. The main goal of this paper is to review recently published articles on dry and wet (liquid and vapor) torrefaction technologies for biomass and compare the similarities and differences among them. There is a more significant amount of studies on dry torrefaction compared to wet torrefaction, however the number of liquid torrefaction articles has increased significantly in the last year. Torrefied products produced from both methods are hydrophobic, possess lower moisture contents, increased energy density, and increased higher heating values, which improves torrefied biomass to a point, where it is more comparable to the characteristics of coal. Wet or hydrothermal torrefaction produces more energy dense products at lower temperatures and lower residence times compared to dry torrefaction, however design costs due to the presence of high pressure and increased transportation costs of wet biomass, are currently limiting the development of wet torrefaction. Application of dry and wet torrefaction depends on the moisture contents of the biomass; wet torrefaction is preferred for biomass with high moisture contents.